Bilateral Rolandic operculum processing underlying heartbeat awareness reflects changes in bodily self‐consciousness. (4th May 2017) - Blefari, Maria Laura; Martuzzi, Roberto; Salomon, Roy; Bello‐Ruiz, Javier; Herbelin, Bruno; Serino, Andrea; Blanke, Olaf
Abstract: Exteroceptive bodily signals (including tactile, proprioceptive and visual signals) are important information contributing to self‐consciousness. Moreover, prominent theories proposed that visceral signals about internal bodily states are equally or even more important for self‐consciousness. Neuroimaging studies have described several brain regions which process signals related to bodily self‐consciousness (BSC) based on the integration of exteroceptive signals (e.g. premotor cortex, angular gyrus, supramarginal gyrus and extrastriate body area), and that another brain region, the insula/operculum which is involved in interoception and interoceptive awareness, processes signals critical for self‐awareness. Providing evidence for the integration of exteroceptive and interoceptive bodily signals, recent behavioral experiments have demonstrated that the manipulation of interoceptive (e.g. cardiac) signals, coupled with exteroceptive (e.g. visual) signals, also modulates BSC. Does this integration occur within or outside the structures described above? To this end, we adapted a recently designed protocol that uses cardio‐visual stimulation to induce altered states of BSC to fMRI. Additionally, we measured neural activity in a classical interoceptive task. We found six brain regions (bilateral Rolandic operculum, bilateral supramarginal gyrus, right frontal inferior operculum and left temporal superior gyrus) that were activated differently during the interoception task as opposed to a control task. The brain regions which showed the highest selectivity for BSC based on our cardio‐visual manipulation were found in the bilateral Rolandic operculum. Given our findings, we propose that the Rolandic operculum processes integrated exteroceptive–interoceptive signals that are necessary for interoceptive awareness as well as BSC. Abstract : Viewing a virtual body flashing in synchrony with one's heartbeat induced changes in bodily self‐consciousness (BSC). fMRI results indicated that the Rolandic operculum was differentially activated not only by cardio‐visual related changes in BSC, but also in a cardiac awareness task. These results highlight the role of the Rolandic operculum in processing interoceptive signals and the experience of bodily self‐consciousness.